2017
DOI: 10.1007/978-1-4939-6783-4_2
|View full text |Cite
|
Sign up to set email alerts
|

UniProt Protein Knowledgebase

Abstract: The Universal Protein Resource (UniProt) is a freely available comprehensive resource for protein sequence and annotation data. UniProt is a collaboration between the European Bioinformatics Institute (EMBL-EBI), the SIB Swiss Institute of Bioinformatics and the Protein Information Resource (PIR). Across the three institutes more than 100 people are involved through different tasks such as expert curation, software development and support. This chapter introduces the functionality and data provided by UniProt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
198
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(202 citation statements)
references
References 5 publications
2
198
0
2
Order By: Relevance
“…Various reports suggest that some secretable enzyme families such as pectin lyase, pectin methylesterase and polygalacturonase are found in Gram‐negative bacteria (Abbott and Boraston ). Also, as a result of bioinformatic analyses using the UniProt database according to Pundir et al () we confirmed the presence of polygalacturonic enzymes in Pseudomonas genus such as PglA (polygalacturonase), PehA (glycoside hydrolase), PehB (exo‐poly‐galacturonase signal peptide protein), PehC (polygalacturonase transmembrane protein) and PehX (exo‐poly‐alpha‐ d ‐galacturonosidase) (González and Allen ). Furthermore, some sequences were found related to polygalacturonase enzymes such as polygalacturonase (PglA), endopolygalacturonase (PehX) and glycoside hydrolase family 28 (AdhA) in the Enterobacter and Citrobacter genus.…”
Section: Discussionsupporting
confidence: 67%
“…Various reports suggest that some secretable enzyme families such as pectin lyase, pectin methylesterase and polygalacturonase are found in Gram‐negative bacteria (Abbott and Boraston ). Also, as a result of bioinformatic analyses using the UniProt database according to Pundir et al () we confirmed the presence of polygalacturonic enzymes in Pseudomonas genus such as PglA (polygalacturonase), PehA (glycoside hydrolase), PehB (exo‐poly‐galacturonase signal peptide protein), PehC (polygalacturonase transmembrane protein) and PehX (exo‐poly‐alpha‐ d ‐galacturonosidase) (González and Allen ). Furthermore, some sequences were found related to polygalacturonase enzymes such as polygalacturonase (PglA), endopolygalacturonase (PehX) and glycoside hydrolase family 28 (AdhA) in the Enterobacter and Citrobacter genus.…”
Section: Discussionsupporting
confidence: 67%
“…The remaining transcripts were used in a blastx 72 search using default parameters against the UniProt/SwissProt database 73 . Any transcripts that shared >30% sequence identity with known proteins with an e-value >1E-2 were eliminated.…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…Figures A and B show extracted ion chromatograms for the Na v 1.6‐overexpressed HEK239 cells and mouse brain hippocampus tissues tryptic digests using the selected targeted MRM transitions listed in Table corresponding to eight unique peptides to Na v 1.6. The uniqueness of these peptides to Na v 1.6 was verified by aligning protein sequences of Na v 1.6 with those of other sodium channels (Na v 1.1, 1.2, 1.3, 1.5, 1.7 and 1.8) as well as with other major brain proteins using Uniprot . With the exception of the peptide INQDCELPR all peptides showed three targeted transitions, providing partial evidence of their identity.…”
Section: Resultsmentioning
confidence: 90%